An ontology based knowledge management for a user preference of e-learning system - Srisa-an, Chetneti (2016)
There are many kinds of online electronic courseware services including Google site, Apple’s iTunes U, Moodle web-based courseware, and massive open online courses.Knowledge in electronic courseware is widely available but in an unstructured data.Ontology is a good way to manipulate those unstructured data.This paper is aims to understand a user preference in adopting courseware service in an ontology form.An association rule (Data Mining) is applied to find out factors and conditions that lead to decision to choose a service.Due to its benefit to search engine, OWL format is chosen as a file format for this paper.Our experimental results show high percentages of confidence and lift values above 80% and greater than 1 respectively.From the relationship, we construct an ontology for user preference using OWL format The relationship between ontology knowledge management with user preferences is that knowledge representation represented in Ontology form and then knowledge is organized and acquired via our user preference web-based application.